Euthanasia and assisted suicide: realization or abandonment of self-determination? - Bauer, Axel W. (Ethical challenges in cancer diagnosis and therapy, 2021)
There are undoubtedly sick people who suffer terribly, and of course this should not be. No patient with incurable cancer is to be so tortured for months or years that they want only to die and lack the means to do so. Being unable to die can be worse than death, one might say or think. But until we ourselves have crossed that frontier, we do not know this for certain. To die could be worse than not being able to die. One case is difficult to distinguish from the other. But we pretend we can distinguish them if we praise assisted suicide and euthanasia as solutions to a problem that we not only do not solve, but make worse. Do we need assisted suicide in the face of non-dying skills? The author’s answer is no: we do not need euthanasia, neither in that nor in any other case. The logic of euthanasia itself decrees that it cannot be restricted to exceptional cases, based as it is on the idea that the patient’s autonomy is to be valued more highly than their actual illness. But if autonomy were of absolute value, it could not be limited to cases of severe disease. The reasons which supporters of euthanasia cite for limiting assisted suicide to the most serious cases of illness, therefore, speak against euthanasia in general. Once the first step has been taken, the application can no longer be limited if, on the one hand, the ‘autonomous’ desire for death is superior to any counter-argument, and on the other hand, no state of illness is conceivable that could call into question the alleged autonomy.